County trajectories of pyramid scheme victimization - Greenman, Sarah J. (Crime, law and social change, 2023)
Community-level vulnerability to pyramid scheme fraud may be affected by place-based sources of strain and opportunity. Using national victim data from a pyramid scheme fraud case from 2000-2013, this research explores pyramid scheme adoption with group-based trajectory modeling (GBTM). GBTM is used to look for distinct trajectories of pyramid scheme join rates and to explore the effect of strain, as measured by a county’s Social Vulnerability Index and unemployment rate, and opportunity or protection, as measured by a series of social capital variables, on the group trajectories. Findings suggest that county-level strain, including the county’s Social Vulnerability Index and unemployment rate are related to pyramid scheme victimization, especially early adoption. We also find that social capital variables - which can, in theory, reduce strain or increase opportunity - have a nuanced relationship with fraud victimization. While our findings are drawn from a single pyramid scheme, they point to the potential to analyze case data to inform preventative and monitoring strategies appropriate to local-level characteristics.